2022
DOI: 10.1515/ijnes-2021-0113
|View full text |Cite
|
Sign up to set email alerts
|

Effective factors and challenges of forming transformational education in the nursing education system: a qualitative study

Abstract: Objectives In the nursing education system, evolution is required to train qualified and professionally competent nurses who can face workplace challenges and evolving needs of societies. This study aimed to explore effective factors and challenges of the formation of transformational education in the nursing education system. Methods This was a qualitative study with a grounded theory approach. Twenty-four individuals partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Moreover, instructors in the present study faced challenges such as the time-consuming process of preparing educational materials and checking assignments, fatigue, and limited time to rest. Similarly, previous studies showed that instructors in VE faced time challenges in recording their lectures, revising and updating their educational materials, and learning how to use and produce virtual materials [41][42][43]. Educational authorities need to overcome these shortcomings and challenges through strategies such as the provision of appropriate VE infrastructures, supervision of VE, and production of quality educational materials.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, instructors in the present study faced challenges such as the time-consuming process of preparing educational materials and checking assignments, fatigue, and limited time to rest. Similarly, previous studies showed that instructors in VE faced time challenges in recording their lectures, revising and updating their educational materials, and learning how to use and produce virtual materials [41][42][43]. Educational authorities need to overcome these shortcomings and challenges through strategies such as the provision of appropriate VE infrastructures, supervision of VE, and production of quality educational materials.…”
Section: Discussionmentioning
confidence: 97%